Penerapan Model Kooperatif Tipe Jigsaw dalam Pembelajaran IPAS untuk Meningkatkan Hasil Belajar Siswa Kelas V SDI Bertingkat Kelapa Lima 3 - Sampe, Markus; Koro, Maxsel; Bire Logo, Rini Putri J (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Learning outcomes can provide an overview of the achievement of learning. The Jigsaw type cooperative model is one type that helps students collaborate with peers to explore material and become peer tutors for their group friends. This research aims to improve the learning outcomes of class V SDI Graded Kelapa Lima 3 students on material on ethnic and cultural diversity in Indonesia through the application of the Jigsaw type cooperative learning model. This classroom action research (PTK) uses the Kemmis and Tagart model. Research data was collected using tests and observations and analyzed quantitatively. The findings in this research prove that there is an increase in student learning outcomes after using the jigsaw type cooperative model with an increase of 26% in cycle I and an increase of 39% in cycle II. This increase cannot be separated from the implementation of the jigsaw type cooperative model which can make students actively discuss with their friends, increase learning motivation, a sense of responsibility and student confidence in learning.